Polyvinyl alcohol film and method for manufacturing an optical film using the same

KR103020312B1Active Publication Date: 2026-09-15KURARAY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020227041800
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-06-23
Publication Date
2026-09-15
Estimated Expiration
2041-06-23

Smart Images

  • Figure 112022127401755-PCT00003_ABST
    Figure 112022127401755-PCT00003_ABST
Patent Text Reader

Abstract

The present invention provides a PVA film capable of producing an optical film having excellent optical performance and low shrinkage stress at high temperatures, and a method for producing an optical film using such a PVA film. The polyvinyl alcohol film of the present invention satisfies the following equation for the crystal long period (Ds) obtained from small-angle X-ray scattering measurements performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystal long period (Da) obtained from small-angle X-ray scattering measurements performed before immersion in the mixed solvent. 0.3 ≤ (Ds-Da) / Da < 0.5
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polyvinyl alcohol film and a method for manufacturing an optical film using the same. Background Technology

[0002] A polarizing plate having light transmission and shielding functions is a basic component of a liquid crystal display (LCD) along with a liquid crystal that changes the polarization state of light. A polarizing plate is generally manufactured by producing a polarizing film by performing a dyeing process, a stretching process (uniaxial stretching process), and, if necessary, an additional fixing treatment process with a boron compound, etc. on a polyvinyl alcohol film (hereinafter, "polyvinyl alcohol" may be abbreviated as "PVA"), and then laminating a protective film such as a cellulose triacetic acid (TAC) film onto the surface of the polarizing film.

[0003] LCDs have come to be used in a wide range of applications, including small devices such as electronic desktop calculators and wristwatches, notebook computers, liquid crystal monitors, liquid crystal color projectors, liquid crystal televisions, automotive navigation systems, mobile phones, and measuring instruments used indoors and outdoors. In response to the recent increase in the performance of LCDs, there is a demand for high performance in polarizers, which are components of LCDs. Specifically, there is a demand for polarizers that possess superior optical performance and excellent dimensional stability even at high temperatures. Accordingly, polarizing films used in polarizers are also required to possess superior optical performance (polarization performance) and have low shrinkage stress under high temperatures.

[0004] However, for polarizing films, it is not easy to reduce shrinkage stress at high temperatures while increasing optical performance (polarizing performance). This is because, generally, a trade-off relationship exists between the polarizing performance and shrinkage stress of a polarizing film. In other words, if one attempts to increase the polarizing performance of a polarizing film, the shrinkage stress increases, and if one attempts to reduce the shrinkage stress, the polarizing performance decreases.

[0005] Patent Document 1 describes that a polarizing film with excellent polarizing performance and low shrinkage stress is obtained by using a PVA film containing PVA with an average degree of polymerization of 2500 to 3500 and employing a predetermined cross-linking stretching process. However, even when a polarizing film is manufactured by the method described in Patent Document 1, depending on the film formation conditions of the PVA film, it is difficult to achieve the same polarizing performance and shrinkage stress of the obtained polarizing film, so there is room for improvement from the perspective of the crystal structure of the PVA film.

[0006] Meanwhile, Patent Document 2 describes that by using a PVA film in which the long period obtained by small-angle X-ray scattering and the thickness of the amorphous portion are set to a specific range, a polarizing film is obtained that has excellent in-plane uniformity of polarization performance (degree of polarization, single transmittance) and is suitable for large area and high precision. In addition, Patent Document 3 describes that by using a PVA film in which the crystal long period in water is set to a specific range, a polarizing film with high absorbance in the long wavelength region and further high degree of polarization can be manufactured. However, Patent Documents 2 and 3 do not consider the shrinkage stress of the polarizing film, and naturally, they do not consider the compatibility of the polarization performance and shrinkage stress of the polarizing film. Prior art literature

[0007] Japanese Published Patent Application No. 2017-142347, Japanese Published Patent Application No. 2006-188655, WO2013 / 146147 The problem to be solved

[0008] Therefore, the present invention aims to provide a PVA film capable of producing an optical film having excellent optical performance and low shrinkage stress under high temperature, and a method for manufacturing an optical film using such a PVA film. means of solving the problem

[0009] The inventors, focusing on the change in the crystal structure, particularly the crystal long period, of a PVA film before and after swelling, conducted a thorough examination and discovered that by setting the ratio of the change in the crystal long period before and after immersion of the PVA film in a water / methanol mixed solvent to the crystal long period before immersion within a specific range, an optical film with excellent optical performance and low shrinkage stress at high temperatures can be obtained. Based on this finding, they further conducted more examinations and completed the present invention.

[0010] That is, the present invention relates to the following [1] to [7].

[0011] [1] A PVA film in which the crystal long period (Ds) obtained from small-angle X-ray scattering measurements taken in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystal long period (Da) obtained from small-angle X-ray scattering measurements taken before immersion in the mixed solvent satisfy the following equation.

[0012] 0.3 ≤ (Ds-Da) / Da < 0.5

[0013] [2] A PVA film described in [1] having a crystal long period (Da) of 10.0 to 12.5 nm.

[0014] [3] A PVA film described in [1] or [2], wherein the PVA contained in the above PVA film contains ethylene units, and the content is 1 to 8 mol%.

[0015] [4] A PVA film described in any one of [1] to [3], having an average film thickness of 15 to 60 μm.

[0016] [5] A PVA film described in any one of [1] to [4], which is a base film for manufacturing optical films.

[0017] [6] A method for manufacturing an optical film by uniaxially stretching a PVA film described in any one of [1] to [5].

[0018] [7] A method for manufacturing an optical film as described in [6], comprising a swelling process for swelling a PVA film. Effects of the invention

[0019] The present invention provides a PVA film capable of producing an optical film with excellent optical performance and low shrinkage stress under high temperature, a method for producing an optical film using such a PVA film, and an optical film. Brief explanation of the drawing

[0020] FIG. 1 shows the scattering vector q (nm) at the top of the peak in the scattering curve obtained from small-angle X-ray scattering measurements. -1 This is a reference diagram for setting ). FIG. 2 is a plot showing the polarization degree against shrinkage stress when the single transmittance is 44.0% for the polarizing films obtained in Examples 1 to 3 and Comparative Examples 1 to 3. Specific details for implementing the invention

[0021] The present invention will be described in detail below.

[0022] <PV Film>

[0023] (Small-angle X-ray scattering measurement)

[0024] The PVA film of the present invention satisfies the equation 0.3 ≤ (Ds-Da) / Da < 0.5, wherein the crystal long period (Ds) obtained from small-angle X-ray scattering measurements performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystal long period (Da) obtained from small-angle X-ray scattering measurements performed before immersion in the mixed solvent are 0.3 ≤ (Ds-Da) / Da < 0.5.

[0025] In small-angle X-ray scattering measurements, diffraction is analyzed when X-rays are irradiated onto a sample and scattered or interfered with by electrons surrounding atoms. In particular, by analyzing the diffraction that appears in the low-angle region of 2θ < 10°, the structure of the sample being measured can be evaluated, and it is said that structures of a size of typically several nm to tens of nm can be evaluated. For example, the crystal long period (the average value of the distance between crystals randomly existing in the polymer) of the sample being measured can be evaluated.

[0026] Generally, when X-rays are incident on a regularly arranged material, the X-rays are scattered. The scattered X-rays interfere with each other and reinforce one another in specific directions. According to Bragg’s equation, where d is the interlattice distance, θ is the Bragg angle, and λ is the wavelength of the X-ray, diffracted X-rays resulting from this scattering are observed only in directions satisfying Bragg’s equation 2d·sinθ = nλ.

[0027] A PVA film contains crystalline regions (lamellar crystals) in which the molecular chains of PVA are folded, and amorphous regions in which the molecular chains of PVA are unfolded. Furthermore, in the present invention, the average value of the inter-crystal distances between the crystalline regions (lamellar crystals) is defined as the crystal long period. This crystal long period can be determined from the diffraction peaks of the scattering curve obtained by performing small-angle X-ray scattering measurements on the PVA film. Additionally, when the PVA film is a base film for manufacturing optical films, the diffraction peaks originating from this crystal long period are the scattering vector q (nm -1 ) is 0.5 nm -1 It is generally known to appear in the vicinity.

[0028] (Calculation of long-term decision period)

[0029] In the present invention, a PVA film to be subjected to small-angle X-ray scattering measurement was prepared as follows and used as a measurement sample. First, the PVA film to be subjected to measurement was cut into multiple sheets of 2 cm × 1 cm in size, without distinguishing between the width direction (TD direction) and the machine flow direction (MD direction). After storing these cut PVA films for 24 hours under conditions of a temperature of 20 ℃ and a humidity of 65 %), 10 sheets were stacked in a measurement cell to be used as a measurement sample. Here, the crystal field period obtained from the scattering curve obtained when small-angle X-ray scattering measurement was performed on this measurement sample in air (temperature of 20 ℃, humidity of 65 %) is the crystal field period (Da) described below. In addition, multiple PVA films cut to the same size of 2 cm × 1 cm were immersed in a water / methanol mixed solvent (volume ratio: 2 / 8) for 24 hours, and then 10 of them were stacked in a measurement cell filled with the mixed solvent to serve as a measurement sample. Here, the crystal field period obtained from the scattering curve obtained when small-angle X-ray scattering measurements were performed on this measurement sample is the crystal field period (Ds) described below.

[0030] In preparing the measurement sample, the measurement cell uses a Kapton film with a thickness of 7.5 μm as the window material for the incident light side and the reflected light side, and the gap between the window materials is set to approximately 1.5 mm. By having such a structure, the measurement sample can be sealed within the measurement cell. In addition, by using this measurement cell, the PVA film to be measured can be placed in the mixed solvent in the usual measurement setup of the following measurement device.

[0031] In the present invention, small-angle X-ray scattering measurements were performed using a nanoscale X-ray structure evaluation device "Nano Viewer" (manufactured by Rigaku Co., Ltd.). The measurement conditions are as follows.

[0032] Transmission measurement

[0033] X-ray: CuKα rays

[0034] Wavelength: 0.15418 nm

[0035] Output: 40 kV-20 mA

[0036] 1st slit: φ0.4 mm

[0037] Second slit: φ0.2 mm

[0038] Third slit: φ0.45 mm

[0039] Detector: Semiconductor 2D Detector PILATUS-100K (Measurement area = 33.5×83.8 mm)

[0040] Pixel size: 0.172 mm

[0041] Camera length: 1004.51 mm

[0042] Beam stopper diameter: 4 mm

[0043] X-ray exposure time: 1 hour

[0044] Measurement Mode: Normal Measurement

[0045] Ambient temperature: Room temperature (20 ℃)

[0046] In the measurement of small-angle X-ray scattering of a PVA film, scattering from devices such as slits, air in the X-ray passage section, and the solvent inside the cell overlaps with the scattering from the PVA film; therefore, it is necessary to correct for these scatterings as background. Accordingly, correction was performed by subtracting the scattering intensity of the aforementioned background, calculated separately, from the scattering intensity obtained by measuring the sample. Additionally, from the scattering intensity image of small-angle X-ray scattering measured by a 2D detector, the scattering vector q (nm -1 By integrating the scattering intensity for ) in the azimuthal direction, the scattering vector q (nm -1 The relationship between the 1D profile of ) and scattering intensity I(q) was derived, and the scattering curve was obtained.

[0047] As described above, in the small-angle X-ray scattering measurement of the PVA film, the diffraction peak originating from the crystal long period of the PVA film is, in the scattering curve, the scattering vector q (nm -1 ) is 0.5 nm -1 It appears in the vicinity. In the present invention, the scattering vector q (nm) of the peak top of this diffraction peak -1 The crystal long period (Ds) and crystal long period (Da) were calculated from the value of ). Here, this peak top is the scattering vector q (nm -1 In the range where ) is 0.2 or greater and 1.0 or less, it is an inflection point where the scattering curve becomes convex upward (see Fig. 1).

[0048] The scattering vector q (nm) obtained above -1 The formula for calculating the crystal long period (Ds) and crystal long period (Da) from the value of ) is as follows.

[0049] Crystal long period (nm) = 2π / q

[0050] In the present invention, it is important that the crystal long period (Ds) obtained from small-angle X-ray scattering measurements performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystal long period (Da) obtained from small-angle X-ray scattering measurements performed before immersion in the mixed solvent satisfy the equation 0.3 ≤ (Ds-Da) / Da < 0.5.

[0051] Here, (Ds-Da) / Da represents the rate of increase in the crystal long period before and after immersion in a water / methanol mixed solvent (volume ratio: 2 / 8). By performing small-angle X-ray scattering measurements in a water / methanol mixed solvent (volume ratio: 2 / 8), the state of crystal dissolution at the beginning of swelling when the PVA film is immersed in water can be evaluated. (Ds-Da) / Da (hereinafter referred to as the "rate of increase in the crystal long period") is preferably less than 0.5, and more preferably less than 0.4. (Ds-Da) / Da is preferably 0.3 or higher, and more preferably 0.32 or higher. If the rate of increase in the crystal long period is excessively large, during the swelling process when manufacturing an optical film, the distance between lamellar crystals in the PVA film is likely to expand as the PVA film swells due to a solvent such as water. In other words, it is thought that the interaction of PVA molecular chains tends to be reduced in the amorphous regions existing between the lamellar crystals in the PVA film. As a result, during the stretching process when manufacturing an optical film, the stretching stress applied to the PVA film does not sufficiently contribute to the orientation of the PVA molecular chains, and there is a concern that the optical performance of the resulting optical film may be lowered. On the other hand, if the growth rate of the crystal long period is excessively small, it is thought that the amorphous regions in the PVA film are difficult to swell with a solvent such as water during the swelling process when manufacturing an optical film. That is, during the stretching process when manufacturing an optical film, the lamellar crystals in the PVA film are difficult to dissolve, and the stretching stress tends to concentrate in the crystalline regions. As a result, the PVA molecular chains are not sufficiently oriented in the amorphous regions of the PVA film, and there are cases where the optical performance and shrinkage stress of the resulting optical film cannot be achieved simultaneously.

[0052] In the present invention, the crystal long period (Da) of the PVA film, obtained from small-angle X-ray scattering measurements taken before immersion in a water / methanol mixed solvent (volume ratio: 2 / 8), is preferably 10.0 nm or greater. Additionally, the crystal long period (Da) is preferably 12.5 nm or less. Here, the crystal long period (Da) is obtained by taking small-angle X-ray scattering measurements in air (temperature 20 ℃, humidity 65 %) before immersion in a water / methanol mixed solvent (volume ratio: 2 / 8). It is more preferable that the lower limit of the crystal long period (Da) is 11.0 nm. It is more preferable that the upper limit of the crystal long period (Da) is 12.3 nm. If the crystal long period (Da) is less than 10.0 nm, it is presumed to be a crystal structure in which the thickness of the lamellar crystals in the PVA film is small. If the thickness of the lamellar crystals is small, microcrystalline lamellar crystals within the PVA film are prone to dissolving when the PVA film is immersed in a solvent such as water during the swelling process for manufacturing an optical film. As a result, the PVA film becomes flexible, and there is a risk that wrinkles may easily form in the PVA film during the swelling process. On the other hand, if the crystal long period (Da) is greater than 12.5 nm, it is presumed that the thickness of the lamellar crystals within the PVA film is large, or that the crystal structure has a long distance between lamellar crystals and a large amorphous region. In the former case, the lamellar crystals within the PVA film are not sufficiently dissolved during the swelling process for manufacturing an optical film, and the stretching tension of the PVA film tends to increase during the stretching process for manufacturing an optical film. As a result, there is a risk that the shrinkage stress of the resulting optical film may increase. In the latter case, during the swelling process when manufacturing an optical film, when the PVA film is immersed in a solvent such as water, the amorphous portion of the PVA film is prone to accepting water.As a result, the PVA film becomes flexible, which lowers the stretching tension of the PVA film during the stretching process when manufacturing the optical film, raising concerns that the optical performance of the resulting optical film may become insufficient.

[0053] In the present invention, the crystal long period (Ds) obtained from small-angle X-ray scattering measurements performed in a water / methanol mixed solvent (volume ratio: 2 / 8) is preferably 12.0 nm or more. Additionally, the crystal long period (Ds) is preferably 18.0 nm or less. The lower limit of the crystal long period (Ds) is more preferably 13.0 nm. The upper limit of the crystal long period (Ds) is more preferably 17.0 nm. If the crystal long period (Ds) exceeds 18.0 nm, the molecular chains of PVA are prone to expanding when the PVA film is immersed in a solvent such as water during the swelling process when manufacturing an optical film, and there is a risk that the moisture and heat resistance of the resulting optical film will deteriorate. On the other hand, if the crystal length period (Ds) is less than 12.0 nm, it is difficult for water to enter the amorphous portion of the PVA film when the PVA film is immersed in a solvent such as water during the swelling process when manufacturing an optical film. As a result, the stretching tension of the PVA film increases during the stretching process when manufacturing an optical film, and there is a risk that the shrinkage stress of the resulting optical film will increase.

[0054] In the present invention, methods for adjusting the crystal long period (Ds) and crystal long period (Da) and controlling the rate of increase of the crystal long period to the above range include: (1) a method of adjusting the crystal state of PVA by controlling the extrusion, drying, and heating conditions when forming the film; (2) a method of adjusting the expansion of the amorphous portion in the PVA film by adjusting the degree of interaction between molecular chains of PVA by the type of PVA (degree of saponification, amount of modification, etc.); (3) a method of adjusting the size of the lamellar crystals by adding a plasticizer, etc.; (4) a method of adjusting the crystal state of PVA or the expansion of the amorphous portion by adjusting the cross-linking structure between molecular chains of PVA by adding a cross-linking agent, etc.; and a method of adjusting by a combination of these.

[0055] When the increase rate of the crystal long period is controlled to the above range by the method of (1) above, the discharge conditions when forming the film are preferably such that, for example, the volatile fraction of the film-forming solution is 10 mass% or more and 40 mass% or less. In addition, the shear rate at the outlet of the film-forming discharge device is 75 s -1 That's all, and 1000 s -1 It is preferable that the drying conditions when forming the film are such that, for example, the surface temperature of the support material that holds the film-forming solution is preferably 60°C or higher and 100°C or lower. The temperature of the hot air sprayed on the non-contact side of the PVA film on the support material is preferably 50°C or higher and 150°C or lower. The temperature of the drying oven or the average temperature of the drying roll (average value of the surface temperature of the drying roll) is preferably 40°C or higher and 110°C or lower. The heating conditions when forming the film are such that, for example, the surface temperature of the heat treatment roll is preferably 135°C or lower.

[0056] When the rate of increase of the crystal long period is controlled to the above range by the method of (2) above, the degree of saponification of PVA is preferably, for example, 85 mol% or more and 95 mol% or less. In addition, the amount of modification of PVA (the ratio of modification into monomers other than polyvinyl alcohol units) is preferably, for example, 0.3 mol% or more and 8 mol% or less.

[0057] When controlling the increase rate of the crystal long period to the above range by the method of (3) above, it is preferable that the content of the plasticizer be 2 parts by mass or more and 20 parts by mass or less per 100 parts by mass of PVA. In addition, it is preferable to use ethylene glycol, glycerin, diethylene glycol, and diglycerin as the plasticizer.

[0058] (PVA)

[0059] As the PVA contained in the PVA film of the present invention, a polymer prepared by saponifying a vinyl ester polymer obtained by polymerizing vinyl ester monomers may be used. Examples of vinyl ester monomers include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerianate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, vinyl versatate, etc. Among those described above, vinyl acetate is preferred as the vinyl ester monomer.

[0060] The vinyl ester polymer is not particularly limited, but a polymer obtained using only one or two or more vinyl ester monomers as monomers is preferred, and a polymer obtained using only one vinyl ester monomer as monomers is more preferred. In addition, the vinyl ester polymer may be a copolymer of one or two or more vinyl ester monomers and another monomer capable of copolymerizing with one or two or more vinyl ester monomers.

[0061] Among other monomers, ethylene is preferred. That is, the PVA contained in the PVA film of the present invention preferably contains ethylene units. Furthermore, the content of ethylene units is preferably 1 mol% or more based on the total number of moles of structural units constituting the vinyl ester polymer. In addition, the content of ethylene units is preferably 8 mol% or less, and more preferably 5 mol% or less. By having the content of ethylene units within the above range, the optical performance and shrinkage stress of the obtained optical film can be achieved. Although the reason is not necessarily clear, it is presumed that during the dyeing process when manufacturing the optical film, the dye during the dyeing process is easily adsorbed to the hydrophobic ethylene units in the PVA film, and the orientation of the adsorbed dye is increased by the stretching stress applied to the PVA film.

[0062] Other monomers include, in addition to ethylene, olefins having 3 to 30 carbon atoms, such as propylene, 1-butene, and isobutene; acrylic acid or its salts; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or its salts; methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; Acrylamide derivatives such as acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidepropanesulfonic acid or its salt, acrylamidepropyldimethylamine or its salt, N-methylolacrylamide or its derivatives; methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid or its salt, methacrylamidepropyldimethylamine or its salt, N-methylolmethacrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; Examples include vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanide such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salts, esters, or acid anhydrides; itaconic acid or its salts, esters, or acid anhydrides; vinylsilyl compounds such as vinyltrimethoxysilane; and isopropenyl acetate.In addition, vinyl ester polymers may have structural units derived from one or more of the other monomers described above.

[0063] The proportion of structural units derived from monomers other than ethylene is not necessarily limited as long as it does not interfere with the effects of the present invention, but based on the total number of moles of structural units constituting the vinyl ester polymer, it is preferably 15 mol% or less, more preferably 5 mol% or less, even more preferably 1 mol% or less, and in some cases, even more preferably 0.1 mol% or less.

[0064] The degree of polymerization of PVA is not particularly limited, but it is preferable that it be 1,000 or higher. Additionally, the degree of polymerization of PVA is preferable that it be 8,000 or lower. From the perspective of improving the optical performance and moisture-heat resistance of the resulting optical film, the degree of polymerization of PVA is more preferable to be 1,500 or higher, and more preferable to be 2,000 or higher. Meanwhile, from the perspective of increasing the productivity of PVA, the upper limit of the degree of polymerization is more preferable to be 5,000 or lower, and even more preferable to be 4,000 or lower.

[0065] Here, the degree of polymerization refers to the average degree of polymerization measured in accordance with the specifications of JIS K 6726-1994. That is, in the present invention, the degree of polymerization (Po) can be obtained by the following formula from the intrinsic viscosity [η] (deciliter / g) measured in water at 30°C after re-saponifying and purifying the residual acetic acid groups of PVA.

[0066] Degree of polymerization Po = ([η]×10 4 / 8.29) (1 / 0.62)

[0067] In the present invention, the lower limit of the degree of saponification of PVA is preferably 98.7 mol%, more preferably 99.0 mol%, even more preferably 99.5 mol%, particularly preferably 99.8 mol%, and preferably 99.9 mol%. By having a degree of saponification equal to or greater than the above lower limit, an optical film with excellent optical performance and moisture-heat resistance is obtained. Meanwhile, although there is no particular limit on the upper limit of the degree of saponification, it is preferably 99.99 mol% or less from the perspective of PVA productivity.

[0068] Here, the degree of saponification of PVA refers to the ratio (mol%) of the number of moles of vinyl alcohol units to the total number of moles of vinyl alcohol units and structural units (typically vinyl ester monomer units) that can be converted into vinyl alcohol units by saponification. The degree of saponification of PVA can be measured in accordance with the description in JIS K 6726-1994.

[0069] The PVA film of the present invention may contain one type of PVA alone, or may contain two or more types of PVA that differ from each other in degree of polymerization, degree of saponification, degree of modification, etc.

[0070] The upper limit of the ratio of PVA content in the PVA film is not particularly limited. Meanwhile, the lower limit of the ratio of PVA content is preferably 50 mass%, more preferably 80 mass%, and even more preferably 85 mass%.

[0071] (Plasticizer)

[0072] The PVA film of the present invention preferably contains a plasticizer. By containing a plasticizer, the stretchability of the PVA film can be improved during the stretching process when manufacturing an optical film. Polyhydric alcohols are preferred as plasticizers. Examples of polyhydric alcohols include ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, trimethylolpropane, etc. Among these, glycerin is preferred in terms of the effect of improving stretchability. The plasticizer may be used as a single type or in combination of two or more types.

[0073] By adjusting the content of the plasticizer in the PVA film, the amount or size of the lamellar crystals can be controlled. Although it varies depending on the primary structure of the PVA molecular chain, generally, compared to a PVA film without a plasticizer, a PVA film containing a small amount of plasticizer is more likely to undergo crystal growth through heat treatment. This is presumed to be because the small amount of plasticizer makes it easier for PVA molecules within the PVA film to move, making it easier to adopt a more energetically stable crystal structure. Furthermore, as crystal growth of the PVA film progresses, the size of the lamellar crystals within the PVA film increases, and the crystal long period (Da) tends to increase. On the other hand, if the PVA film contains an excess amount of plasticizer, crystal growth tends to be inhibited. This is presumed to be because the amount of plasticizer interacting with the hydroxyl groups of the PVA molecules increases, weakening the interactions between PVA molecules. In addition, if the PVA film contains a plasticizer, the amorphous portion of the PV film becomes more receptive to water, and the rate of increase in the crystal long period tends to increase.

[0074] From the perspective of adjusting the size of lamellar crystals in the PVA film to an appropriate range and controlling the crystal long period (Da) and the growth rate of the crystal long period, it is preferable that the plasticizer content be 2 parts by mass or more per 100 parts by mass of PVA. Additionally, it is preferable that the plasticizer content be 20 parts by mass or less per 100 parts by mass of PVA. In both cases where the plasticizer content is less than 2 parts by mass and where it exceeds 20 parts by mass per 100 parts by mass of PVA, the size of the lamellar crystals in the PVA film tends to become excessively small. As a result, the crystal long period (Da) becomes smaller, and there is a risk that the growth rate of the crystal long period of the PVA film will fall outside the predetermined range. It is more preferable that the plasticizer content be 5 parts by mass or more per 100 parts by mass of PVA, and even more preferable that it be 8 parts by mass or more. In addition, the content of the plasticizer is more preferably 17 parts by mass or less per 100 parts by mass of PVA, and even more preferably 15 parts by mass or less.

[0075] (Surfactant)

[0076] The PVA film of the present invention preferably contains a surfactant. By manufacturing a PVA film using a film-forming stock solution containing a surfactant, the film-forming properties of the PVA film are improved. As a result, the occurrence of non-uniformity in the thickness of the PVA film is suppressed, and the peeling of the PVA film from the metal roll or belt used for film formation becomes easier. When manufacturing a PVA film from a film-forming stock solution containing a surfactant, the resulting PVA film contains the surfactant.

[0077] The type of surfactant is not particularly limited, but anionic surfactants and nonionic surfactants are preferred from the perspective of peelability of the PVA film from a metal roll or belt.

[0078] Examples of anionic surfactants include carboxylic acid types such as potassium laurate; sulfate ester types such as polyoxyethylene lauryl ether sulfate and octyl sulfate; and sulfonic acid types such as dodecylbenzene sulfonate.

[0079] Examples of nonionic surfactants include alkyl ether types such as polyoxyethylene oleyl ether; alkylphenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkylamine types such as polyoxyethylene laurylamino ether; alkylamide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; and allylphenyl ether types such as polyoxyalkylene allylphenyl ether.

[0080] Surfactants can be used as a single type or in combination of two or more types.

[0081] When the PVA film contains a surfactant, the lower limit of the surfactant content in the PVA film is preferably 0.01 parts by mass per 100 parts by mass of PVA, more preferably 0.02 parts by mass, and even more preferably 0.05 parts by mass. By making the surfactant content above the above lower limit, the film-forming and peelability of the PVA film are further improved. Meanwhile, the upper limit of the surfactant content in the PVA film is preferably 0.5 parts by mass per 100 parts by mass of PVA, more preferably 0.3 parts by mass, and even more preferably 0.2 parts by mass. By making the surfactant content below the above upper limit, it is possible to suppress the surfactant from bleeding out onto the surface of the PVA film, which causes blocking and reduces handling performance.

[0082] (other additives, etc.)

[0083] The PVA film of the present invention may additionally contain, as necessary, additives such as fillers, processing stabilizers including copper compounds, weathering stabilizers, colorants, ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, other thermoplastic resins, lubricants, fragrances, defoaming agents, deodorizing agents, fillers, release agents, mold release agents, reinforcing agents, crosslinking agents, antifungal agents, preservatives, and crystallization rate retardants.

[0084] In the PVA film of the present invention, the proportion of the total of PVA, plasticizer, and surfactant is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and in some cases, more preferably 99 mass% or more. Since the PVA film of the present invention is substantially composed of PVA, plasticizer, and surfactant, when a polarizing film is manufactured using the PVA film of the present invention, a polarizing film with excellent polarization performance can be obtained.

[0085] (Shape, physical properties, etc.)

[0086] The PVA film of the present invention is a so-called raw film for manufacturing optical films, used as a material for optical films. However, the PVA film of the present invention is not limited to being in a roll shape.

[0087] The average thickness of the PVA film of the present invention is not particularly limited. The lower limit of the average thickness of the PVA film is preferably 1 μm, more preferably 5 μm, even more preferably 10 μm, and particularly preferably 15 μm. By having an average thickness greater than or equal to the lower limit, breakage of the PVA film can be suppressed during the stretching process when manufacturing an optical film. Meanwhile, the upper limit of the average thickness is preferably 60 μm, more preferably 50 μm, even more preferably 45 μm, and even more preferably 35 μm. By having an average thickness less than or equal to the upper limit, the effects of the present invention can be fully exhibited. Furthermore, "average thickness" refers to the average value of thicknesses measured at any five points (hereinafter, the same applies to average thickness).

[0088] The PVA film of the present invention may be a single-layer film consisting of one layer of PVA, or a multilayer film including one layer of PVA. However, when the PVA film of the present invention is used as a base film for manufacturing a polarizing film, it is preferable that it be a single-layer film. When the PVA film of the present invention is included as a PVA layer of a multilayer film, the lower limit of the average thickness of the PVA layer is preferably 1 μm, more preferably 5 μm, even more preferably 10 μm, and particularly preferably 15 μm. By having an average thickness greater than or equal to the lower limit, breakage of the PVA film can be suppressed during the stretching process when manufacturing an optical film. Furthermore, the upper limit of the average thickness of the PVA layer is preferably 60 μm, more preferably 50 μm, even more preferably 45 μm, and even more preferably 35 μm. By having an average thickness below the above upper limit, the effects of the present invention can be fully exerted.

[0089] A multilayer film refers to a film having two or more layers. The number of layers in a multilayer film may be five or fewer, or three or fewer. Examples of multilayer films include laminated films having a laminated structure of a base resin layer and a PVA layer. The average thickness of the base resin layer is preferably, for example, 20 μm or more. Additionally, the average thickness of the base resin layer is preferably, for example, 500 μm or less. In the multilayer film, the base resin layer is preferably capable of uniaxial stretching together with the PVA layer. As the resin constituting the base resin layer, polyester, polyolefin, etc., may be used. Among these, amorphous polyester is preferred, and polyethylene terephthalate and amorphous polyester obtained by copolymerizing polyethylene terephthalate with copolymer components such as isophthalic acid and 1,4-cyclohexanedimethanol are preferably used. An adhesive layer may be formed between the base resin layer and the PVA layer.

[0090] The width of the PVA film of the present invention is not particularly limited and can be determined according to its application, etc. For example, the lower limit of the width of the PVA film is preferably 3 m. Since the lower limit of the width is 3 m, it is suitable for applications in liquid crystal televisions or liquid crystal monitors, where large screens are becoming more common recently. On the other hand, the upper limit of the width of the PVA film is preferably 7 m. By setting the upper limit of the width to 7 m, when manufacturing optical films such as polarizing films using commercially available equipment, a stretching process (uniaxial stretching process) can be efficiently performed.

[0091] The degree of swelling of the PVA film of the present invention is preferably 140% or more from the perspective of productivity or optical performance of the obtained optical film. In addition, the degree of swelling of the PVA film of the present invention is preferably 400% or less. The lower limit of the degree of swelling is more preferably 170%, more preferably 180%, and particularly preferably 190%. In addition, the upper limit of the degree of swelling is more preferably 220%, and more preferably 210%. The degree of swelling of the PVA film can be adjusted to a smaller value, for example, by increasing the temperature of the heat treatment of the PVA film.

[0092] Here, "degree of swelling of PVA film" refers to the value obtained by the following formula.

[0093] Swelling degree (%) = 100×N / M

[0094] In the formula, N represents the mass (g) of a sample taken from a PVA film after immersing it in distilled water at 30°C for 30 minutes and removing the water from the surface. M represents the mass (g) of a sample after drying the sample in a dryer at 105°C for 16 hours.

[0095] The PVA film of the present invention is typically a film that is not substantially stretched (a non-stretched film, an unstretched film). In addition, the in-plane phase difference of the PVA film is preferably 100 nm or less, and more preferably 50 nm or less. Typically, an optical film can be obtained by stretching the PVA film of the present invention (uniaxial stretching or biaxial stretching).

[0096] According to the PVA film of the present invention, an optical film having excellent optical performance and low shrinkage stress under high temperatures can be manufactured. Examples of optical films that can be manufactured by the PVA film of the present invention include polarizing films, phase difference films, viewing angle enhancement films, brightness enhancement films, etc., and it is preferable that it be a polarizing film.

[0097] <PVA 필름의 제조 방법>

[0098] In the present invention, the film-forming method for a PVA film can be performed by any method, such as a flexible film-forming method, a wet film-forming method (extrusion into a solvent-free solution), a dry-wet film-forming method, a gel film-forming method (a method of obtaining a PVA-based polymer film by first cooling and gelling the film-forming solution and then extracting and removing the solvent), or a combination thereof, using a film-forming solution homogenized by adding a solvent, additives, etc., to PVA, or by a melt extrusion film-forming method or an inflation molding method, in which the film-forming solution is obtained using an extruder, etc., and then extruded through a T-die, etc. Among these, the flexible film-forming method and the melt extrusion film-forming method are preferred because they allow for obtaining a homogeneous film with good productivity. Below, the flexible film-forming method or the melt extrusion film-forming method for a PVA film will be described.

[0099] When a PVA film is produced by a flexible film-making method or a melt extrusion film-making method, the above-mentioned film-making solution is flexible into a film shape on a support such as a metal roll or a metal belt, and solidifies into a film by heating to remove the solvent. The solidified film is peeled off from the support, dried by a drying roll or a drying oven as needed, further heat-treated as needed, and wound up to obtain a long PVA film in the shape of a roll.

[0100] Crystallization proceeds during heating and drying on the support (hereinafter referred to as "PVA film"). In particular, when the film-making solution is heated while having a high volatile fraction (moisture content), the mobility of the PVA molecular chains in the film-making solution (PVA film) increases, and crystallization proceeds. As a result, the amount of lamellar crystals in the PVA film tends to increase, and the crystal long period (Da) tends to decrease. Here, if the drying speed is too fast, the crystallization of the PVA film does not proceed sufficiently, so the amount of lamellar crystals decreases and the crystal long period (Da) tends to increase. On the other hand, if the drying speed is too slow, crystal growth of the PVA film proceeds, the size of the lamellar crystals increases, and the crystal long period (Da) tends to increase. In addition, if the amount of heat applied is excessive, the size of the lamellar crystals in the PVA film tends to increase, the crystal long period (Da) tends to become excessively large, or the rate of increase of the crystal long period tends to become excessively small.

[0101] The volatile fraction of the film-forming solution (the concentration of volatile components, such as solvents, that are removed by volatilization or evaporation during film formation, etc.) is preferably 50 mass% or more, and more preferably 55 mass% or more. The volatile fraction of the film-forming solution is preferably 90 mass% or less, and more preferably 80 mass% or less. If the volatile fraction is less than 50 mass%, the viscosity of the film-forming solution increases, which may make it difficult to form a PVA film. On the other hand, if the volatile fraction concentration exceeds 90 mass%, the viscosity decreases, and the uniformity of the PVA film thickness is easily compromised.

[0102] Here, the term "volatile fraction of the film-forming solution" in the present invention refers to the volatile fraction calculated by the following formula.

[0103] Volatility fraction of film-forming solution (mass%) = {(Wa-Wb) / Wa}×100

[0104] (In the formula, Wa represents the mass (g) of the film-forming stock solution, and Wb represents the mass (g) of the film-forming stock solution of Wa (g) when dried in an electric dryer at 105°C for 16 hours.)

[0105] There are no specific restrictions on the method of adjusting the film-making solution, and examples include a method of dissolving PVA and additives such as plasticizers and surfactants in a melting tank, or a method of melt-mixing PVA in a hydrated state together with plasticizers and surfactants when using a single-screw or twin-screw extruder.

[0106] When a PVA film is formed using a flexible film-forming method or a melt extrusion film-forming method, the above-mentioned film-forming solution is flexible into a film shape on a support such as a metal roll or metal belt from a film-forming discharge device, and solidifies to form a film by heating and removing the solvent.

[0107] The PVA film of the present invention has a crystal long-period growth rate within a specific range before and after immersion in a water / methanol mixed solvent (volume ratio: 2 / 8). This growth rate is presumed to be influenced by the degree of entanglement of PVA molecular chains in the amorphous regions existing between the lamellar crystals in the PVA film. Therefore, the growth rate of the crystal long-period of the PVA film can be controlled by adjusting the shear rate at the outlet of the film-forming extrusion device, where the film-forming solution is subjected to strong shear force. In this regard, the shear rate at the outlet of the film-forming extrusion device is 75 s -1 It is desirable to be more than 100 s -1 It is more desirable to be above this, and 125 s -1 It is more desirable that it be above. In addition, the shear rate at the outlet of the film-shaped discharge device is 1000 s -1 It is desirable that it be less than or equal to 900 s -1 It is more desirable that it be less than or equal to 800 s -1It is more desirable that it be below the above upper limit. By keeping the shear rate below the above upper limit, it is possible to prevent the growth rate of the crystal long period from becoming excessively small. On the other hand, by keeping the shear rate above the above lower limit or higher, it is possible to prevent the growth rate of the crystal long period from becoming excessively large.

[0108] In the present invention, the shear rate at the outlet of the film-shaped discharge device refers to the shear rate at the wall surface of the film-forming liquid flow path in the die lip in the case of a general T die or I die, and can be calculated using the following formula.

[0109] γ = 6Q / Wh 2

[0110] Here, γ is the shear rate at the wall (s -1 ), W is the width of the die lip (cm), h is the opening of the die lip (cm), and Q is the discharge velocity of the film-forming solution from the die lip (cm 3 It means / s).

[0111] It is preferable that the surface temperature of the support that holds the film-forming solution be 50°C or higher. Additionally, it is preferable that the surface temperature of the support that holds the film-forming solution be 110°C or lower. If the surface temperature is below 50°C, the time required to dry the film-forming solution increases, and productivity tends to decrease. On the other hand, if the surface temperature exceeds 110°C, there is a tendency for abnormalities to occur on the film surface of the PVA film due to foaming, etc. Furthermore, as the film-forming solution dries rapidly, the crystallization of the PVA film does not proceed sufficiently, resulting in a decrease in the amount of lamellar crystals and a tendency for the crystal long period (Da) to increase. From the perspective of making it easier to control the rate of increase of the crystal long period of the PVA film, it is preferable that the surface temperature of the support be 60°C or higher, and more preferable that it be 65°C or higher. Additionally, it is preferable that the surface temperature of the support be 100°C or lower, and more preferable that it be 95°C or lower.

[0112] While heating the PVA film on the support, the drying speed may be controlled by uniformly spraying hot air with a wind speed of 1 to 10 m / sec over the entire area on the non-contact side of the PVA film. The temperature of the hot air sprayed on the non-contact side is preferably 50°C or higher, and more preferably 70°C or higher, in terms of drying efficiency and drying uniformity. In addition, the temperature of the hot air sprayed on the non-contact surface is preferably 150°C or lower, and more preferably 120°C or lower, in terms of drying efficiency and drying uniformity.

[0113] The PVA film is preferably dried on a support to a volatile fraction of 5 to 50 mass%, then peeled off, and further dried as needed. There are no particular restrictions on the drying method, and methods such as contacting it with a drying oven or drying rolls may be used. When drying with multiple drying rolls, it is preferable to alternately contact one side of the film with the other side of the drying rolls to ensure uniformity on both sides. The number of drying rolls is preferably 3 or more, more preferably 4 or more, and even more preferably 5 or more. Furthermore, the number of drying rolls is even more preferably 30 or fewer. The upper limit of the temperature of the drying oven or the average temperature of the drying rolls (average value of the surface temperature of the drying rolls) is preferably 110°C, more preferably 100°C, more preferably 90°C, and even more preferably 85°C. If the temperature of the drying oven or the average temperature of the drying roll is excessively high, crystal growth of the PVA film proceeds, and the size of the lamellar crystals in the PVA film tends to increase. As a result, the crystal long period (Da) increases, and there is a risk that the rate of increase of the crystal long period may become excessively small. Meanwhile, the lower limit of the temperature of the drying oven or the average temperature of the drying roll is preferably 40°C, more preferably 45°C, and even more preferably 50°C. If the temperature of the drying oven or the average temperature of the drying roll is excessively low, crystal growth of the PVA film becomes insufficient, and the size of the lamellar crystals in the PVA film tends to decrease. As a result, there is a risk that the crystal long period (Da) may become excessively small or the rate of increase of the crystal long period may become excessively large.

[0114] For the PVA film after drying, additional heat treatment may be performed as needed. By performing heat treatment, the strength, degree of swelling, and birefringence of the PVA film can be adjusted. It is preferable that the surface temperature of the heat treatment roll for performing heat treatment be 60°C or higher. In addition, it is preferable that the surface temperature of the heat treatment roll be 135°C or lower, and more preferable that it be 130°C. If the surface temperature of the heat treatment roll is excessively high, the amount of heat applied is excessively high, and there is a tendency for the size of the lamellar crystals in the PVA film to increase, the crystal long period (Da) to become excessively large, or the rate of increase of the crystal long period to become excessively small.

[0115] The PVA film manufactured in this manner is further subjected to moisture control treatment, cutting of both ends (edges) of the film as needed, wound into a roll shape on a cylindrical core, and moisture-proof packaged to become a product.

[0116] Although the volatile fraction of the PVA film finally obtained by the series of treatments described above is not necessarily limited, it is preferable that the volatile fraction of the PVA film be 1 mass% or more, and more preferable that it be 2 mass% or more. In addition, it is preferable that the volatile fraction of the PVA film be 5 mass% or less, and more preferable that it be 4 mass% or less.

[0117] In addition, when the PVA film of the present invention is a multilayer film, the multilayer film can be manufactured, for example, by applying a film-forming solution onto a substrate resin film (substrate resin layer). At this time, in order to improve the adhesion between the PVA layer and the substrate resin layer, the surface of the substrate resin film may be modified, or an adhesive may be applied to the surface of the substrate resin film.

[0118] Method for manufacturing optical film

[0119] The method for manufacturing an optical film according to the present invention comprises a process of uniaxially stretching the PVA film described above. Hereinafter, as an example of a method for manufacturing an optical film, a method for manufacturing a polarizing film will be specifically explained.

[0120] A method for manufacturing a polarizing film may include a dyeing process for dyeing a PVA film, a stretching process for uniaxial stretching, and, if necessary, a swelling process for further swelling, a crosslinking process for crosslinking, a fixing process for fixing, a washing process for washing, a drying process for drying, and a heat treatment process for heat treatment. In this case, the order of each process is not particularly limited, but for example, it may be carried out in the order of a swelling process, a dyeing process, a crosslinking process, a stretching process, and a fixing process. In addition, one or more processes may be carried out simultaneously, or each process may be carried out two or more times. In particular, the PVA film of the present invention is useful as a film used in a method for manufacturing a polarizing film having a swelling process because it can suppress the occurrence of swelling wrinkles during the swelling process.

[0121] The swelling process can be carried out by immersing a PVA film in a swelling treatment bath containing water, etc. The temperature of the swelling treatment bath is preferably 20°C or higher, more preferably 22°C or higher, and even more preferably 25°C or higher. In addition, the temperature of the swelling treatment bath is preferably 55°C or lower, more preferably 50°C or lower, and even more preferably 45°C or lower. Furthermore, the immersion time in the swelling treatment bath is preferably, for example, 0.1 minutes or more, and more preferably 0.5 minutes or more. The immersion time in the swelling treatment bath is preferably, for example, 5 minutes or less, and more preferably 3 minutes or less. In addition, the water used in the swelling treatment bath is not limited to pure water, but may be an aqueous solution in which various components are dissolved, or a mixture of water and an aqueous medium.

[0122] The dyeing process can be carried out by contacting a PVA film with a solution (dyeing bath) containing a dichroic pigment. It is common to use iodine-based pigments as the dichroic pigment. The timing of dyeing may be at any stage before, during, or after uniaxial stretching. As for the dyeing bath, a solution containing iodine and potassium iodide is preferred, and this solution is preferably an aqueous solution. The concentration of iodine in the dyeing bath is preferably 0.01 mass% or more. Additionally, the concentration of iodine is preferably 0.5 mass% or less. The concentration of potassium iodide is preferably 0.01 mass% or more. Additionally, the concentration of potassium iodide is preferably 10 mass% or less. Furthermore, the temperature of the dyeing bath is preferably 20°C or higher, and more preferably 25°C or higher. The temperature of the dyeing treatment bath is preferably 50°C or lower, and more preferably 40°C or lower. The dyeing time is preferably 0.2 minutes or longer. In addition, the dyeing time is preferably 5 minutes or less.

[0123] By performing a crosslinking process to crosslink the PVA in the PVA film, the leaching of PVA into water during wet stretching at high temperatures can be effectively suppressed. From this perspective, it is preferable to perform the crosslinking process after the dyeing process and before the stretching process. The crosslinking process can be performed by immersing the PVA film in an aqueous solution (crosslinking treatment bath) containing a crosslinking agent. As the crosslinking agent, one or more types of boron compounds, such as borates of boric acid and borax, may be used. The concentration of the crosslinking agent in the crosslinking treatment bath is preferably 1 mass% or more, more preferably 1.5 mass% or more, and even more preferably 2 mass% or more. Furthermore, the concentration of the crosslinking agent is preferably 15 mass% or less, more preferably 7 mass% or less, and even more preferably 6 mass% or less. By keeping the concentration of the crosslinking agent within the above range, the stretchability of the PV film can be sufficiently maintained. The crosslinking treatment bath may contain potassium iodide, etc. The temperature of the crosslinking treatment bath is preferably 20°C or higher, and more preferably 25°C or higher. In addition, the temperature of the crosslinking treatment bath is preferably 60°C or lower, and more preferably 55°C or lower. By keeping the temperature within the above range, the PVA film can be efficiently crosslinked.

[0124] The stretching process for uniaxially stretching a PVA film may be carried out using either a wet stretching method or a dry stretching method. In the case of the wet stretching method, it may be carried out in an aqueous solution containing boric acid (stretching treatment bath), or in the dyeing treatment bath described above or in the fixing treatment bath described later. In addition, in the case of the dry stretching method, stretching may be carried out at room temperature (25°C), while heating, or in air using a PVA film after absorption. Among these, the wet stretching method is preferred in that it allows for stretching with high uniformity in the width direction, and uniaxial stretching in the stretching treatment bath is more preferable. The concentration of boric acid in the stretching treatment bath is preferably 0.5 mass% or more, more preferably 1.0 mass% or more, and even more preferably 1.5 mass% or more. In addition, the boric acid concentration in the stretching treatment bath is preferably 6.0 mass% or less, more preferably 5.0 mass% or less, and even more preferably 4.0 mass% or less. Furthermore, the stretching treatment bath may contain potassium iodide, and the concentration of potassium iodide is preferably 0.01 mass% or more. In addition, the concentration of potassium iodide is preferably 10 mass% or less. The stretching temperature in uniaxial stretching is preferably 30 ℃ or higher, more preferably 40 ℃ or higher, and even more preferably 50 ℃ or higher. In addition, the stretching temperature in uniaxial stretching is preferably 90 ℃ or lower, more preferably 80 ℃ or lower, and even more preferably 75 ℃ or lower.

[0125] In uniaxial stretching, the stretching ratio (total stretching ratio from a non-stretched PVA film) is preferably 5 times or more, and more preferably 5.5 times or more, from the perspective of the polarization performance of the obtained polarizing film. The upper limit of the stretching ratio is not particularly limited, but the stretching ratio is preferably 8 times or less.

[0126] The maximum elongation stress of the PVA film in uniaxial stretching is 50 N / mm 2 It is desirable that it be less than or equal to 25 N / mm 2 It is more preferable that it be less than or equal to 15 N / mm 2 It is more desirable that it be less than or equal to 10 N / mm 2 It is particularly desirable that it be less than or equal to the following. Here, the maximum elongation stress is the value obtained by dividing the elongation tension of the PVA film applied between adjacent rolls in the elongation treatment bath by the cross-sectional area of ​​the PVA film. At this time, the elongation tension of the PVA film can be measured by a tension roll installed between adjacent rolls in the elongation treatment bath, and when three or more rolls are used in the elongation treatment bath, the maximum value among them is used. In addition, the cross-sectional area of ​​the PVA film is obtained from the unoriented PVA film before it is provided for the manufacture of the polarizing film. By reducing the maximum elongation stress, a polarizing film with low shrinkage stress can be obtained. In addition, typically, the maximum elongation stress is 1 N / mm 2 That is all.

[0127] When uniaxially stretching a long PVA film, there are no particular restrictions on the direction of uniaxial stretching, and uniaxial stretching in the long length direction or transverse uniaxial stretching may be employed. Uniaxial stretching in the long length direction is preferred in that a polarizing film with excellent polarization performance is obtained. Uniaxial stretching in the long length direction can be performed by using a stretching device equipped with a plurality of rolls parallel to each other and changing the peripheral speed between each roll. Meanwhile, transverse uniaxial stretching can be performed using a tenter-type stretching machine.

[0128] In the manufacture of a polarizing film, a fixation treatment process may be performed after the stretching process to strengthen the adsorption of dichroic pigments (such as iodine-based pigments) onto the PVA film. As the fixation treatment bath used for the fixation treatment, an aqueous solution containing one or more types of boron compounds, such as boric acid or borax, may be used. Additionally, if necessary, iodine compounds or metal compounds may be added to the fixation treatment bath. The concentration of the boron-containing compound in the fixation treatment bath is preferably 2 mass% or more, and more preferably 3 mass% or more. Furthermore, the concentration of the boron compound in the fixation treatment bath is preferably 15 mass% or less, and more preferably 10 mass% or less. By keeping the concentration of the boron compound within the above range, the adsorption of dichroic pigments can be strengthened. The temperature of the fixation treatment bath is preferably 15°C or higher, and more preferably 25°C or higher. In addition, the temperature of the fixed treatment bath is preferably 60 ℃ or lower, and more preferably 40 ℃ or lower.

[0129] The cleaning process is generally carried out by immersing the film in distilled water, pure water, an aqueous solution, etc. At this time, from the perspective of improving the polarization performance of the obtained polarizing film, it is preferable to use an aqueous solution (cleaning treatment bath) containing an iodide, such as potassium iodide, as an auxiliary agent. It is preferable that the concentration of the iodide be 0.5 mass% or higher. In addition, it is preferable that the concentration of the iodide be 10 mass% or lower. In addition, it is preferable that the temperature of the cleaning treatment bath be 5°C or higher, more preferable that it be 10°C or higher, and even more preferable that it be 15°C or higher. In addition, it is preferable that the temperature of the cleaning treatment bath be 50°C or lower, more preferable that it be 45°C or lower, and even more preferable that it be 40°C. By setting the temperature of the cleaning treatment bath to the above range, the polarization performance of the obtained polarizing film can be further improved.

[0130] Although the conditions of the drying process are not particularly limited, the drying temperature of the PVA film is preferably 30°C or higher, and more preferably 50°C or higher. In addition, the drying temperature of the PVA film is preferably 150°C or lower, and more preferably 130°C or lower. By drying at a temperature within the above range, it is easy to obtain a polarizing film with excellent dimensional stability at high temperatures.

[0131] In addition, optical films other than polarizing films, such as phase difference films, can also be manufactured by a method comprising a process of uniaxially stretching the PVA film of the present invention. The specific manufacturing method may employ conventionally known methods other than using the PVA film of the present invention.

[0132] When the optical film of the present invention is a polarizing film, it is preferable that the dichroism ratio (R) of the polarizing film is 100 or higher. It is more preferable that the dichroism ratio (R) is 150 or higher, and even more preferable that it is 160 or higher. This dichroism ratio (R) is, for example, preferably 350 or lower, and preferably 300 or lower.

[0133] The method for calculating the dichroism ratio (R) of a polarizing film is as follows. First, the relationship between the transmittance (T') excluding surface reflection and the single transmittance (T) is given by the following equation (a). At this time, the refractive index of the polarizing film is assumed to be 1.5, and the reflectance at the surface is assumed to be 4%. Meanwhile, the relationship between the transmittance (T'), the degree of polarization (V), and the dichroism ratio (R) is given by the following equation (b). Therefore, after measuring the single transmittance (T) and the degree of polarization (V), the dichroism ratio (R) of the polarizing film can be calculated by solving equations (a) and (b) using those values.

[0134] T' = T / (1-0.04) 2 … (a)

[0135] R = {-ln[T'(1-V)]} / {-ln[T'(1+V)]} … (b)

[0136] From the dichroism ratio (R) of the polarizing film, the degree of polarization (V) at a predetermined single transmittance (T) can be calculated. First, the transmittance (T') at a predetermined single transmittance (T) is obtained from the above equation (a). Then, the degree of polarization (V) at a predetermined single transmittance (T) can be obtained by solving the equation obtained by substituting this transmittance (T') and the dichroism ratio (R) into the following equation (c), which is a modified version of the above equation (b). In the present invention, the degree of polarization (V) at a single transmittance (T) of the polarizing film at 44.0% was obtained by this method.

[0137] T' = [1-V] 1 / (R-1) / [1+V] R / (R-1) … (c)

[0138] The polarizing film obtained as described above is typically used as a polarizing plate by laminating a protective film, which is optically transparent and possesses mechanical strength, onto one or both sides thereof. As the protective film, cellulose triacetic acid (TAC) film, cycloolefin polymer (COP) film, cellulose acetic acid-butyric acid (CAB) film, acrylic film, polyester film, etc., are used. In addition, PVA-based adhesives, urethane-based adhesives, acrylate-based UV-curing adhesives, etc., can be used as adhesives for lamination. That is, the polarizing plate has a polarizing film and a protective film laminated on one or both sides of the polarizing film, either directly or through an adhesive layer.

[0139] A polarizing plate can be used as a component of an LCD by coating it with an adhesive, such as an acrylic-based one, and then laminating it onto a glass substrate. Additionally, a phase difference film, a viewing angle enhancement film, a brightness enhancement film, etc., may be laminated to the polarizing plate.

[0140] Examples

[0141] The present invention will be specifically explained below through examples, but the present invention is not limited in any way by the following examples. Furthermore, the evaluation items and methods employed in the following examples and comparative examples are as follows.

[0142] (1) Crystal long period of PVA film (Ds and Da)

[0143] For the PVA films obtained in the following examples and comparative examples, small-angle X-ray measurements were performed before and after immersion in a water / methanol mixed solvent (volume ratio: 2 / 8). Specifically, first, multiple PVA films were cut into 2 cm × 1 cm pieces without distinguishing between the width direction (TD direction) and the machine flow direction (MD direction). After storing these cut PVA films for 24 hours under conditions of 20°C and 65% humidity, 10 pieces were stacked in a measurement cell to form a measurement sample. Small-angle X-ray scattering measurements were performed on this measurement sample in air (20°C, 65% humidity) to obtain a scattering curve. The scattering vector q (nm) at the peak top of this scattering curve -1 From the value of ), the determination period (Da) was calculated as shown in the following equation.

[0144] Crystal long period (Da) (nm) = 2π / q

[0145] In addition, the PVA films obtained in the following examples and comparative examples were cut into multiple sheets of 2 cm × 1 cm size, without distinguishing between the width direction (TD direction) and the machine flow direction (MD direction). These cut PVA films were immersed in a water / methanol mixed solvent (volume ratio: 2 / 8) for 24 hours, and then 10 sheets were stacked in a measurement cell filled with the mixed solvent to form a measurement sample. Small-angle X-ray scattering measurements were performed on this measurement sample to obtain a scattering curve. The scattering vector q (nm) at the peak top of this scattering curve -1From the value of ), the determination period (Ds) was calculated as shown in the following equation.

[0146] Crystal long period (Ds) (nm) = 2π / q

[0147] (2) Swelling degree of PVA film

[0148] By the above method, the degree of swelling of the PVA films obtained in the following examples and comparative examples was determined.

[0149] (3) Manufacturing of polarizing film

[0150] A polarizing film was prepared using the PVA film obtained in the following examples and comparative examples. First, the PVA film was stretched 2.0 times in the MD direction in pure water (swelling treatment bath) at 25°C, and then stretched in an aqueous solution at 32°C (dyeing treatment bath) containing 0.03 mass% iodine and 0.7 mass% potassium iodide to a total stretching ratio of 2.4 times. Subsequently, it was stretched in an aqueous solution at 32°C (crosslinking treatment bath) containing 2.6 mass% boric acid to a total stretching ratio of 3.0 times, and further stretched in an aqueous solution at 58°C (stretching treatment bath) containing 2.8 mass% boric acid and 5.0 mass% potassium iodide to a total stretching ratio of 6.0 times. Next, it was immersed for 5 seconds in an aqueous solution (washing treatment bath) at 22°C containing 1.5 mass% boric acid and 2.5 mass% potassium iodide, and dried for 4 minutes in a drying oven at 80°C.

[0151] (4) Maximum elongation stress of PVA film in the manufacture of polarizing film

[0152] In the manufacture of the above polarizing film, the stretching tension of the PVA film applied between adjacent rolls in the stretching treatment bath was measured by a tension roll installed between them, and the value divided by the cross-sectional area of ​​the PVA film was set as the maximum stretching stress. At this time, the cross-sectional area of ​​the PVA film was obtained from the unstretched PVA film before being provided for the manufacture of the polarizing film.

[0153] (5) Optical performance of polarizing film

[0154] A rectangular measurement sample was taken from the center of the obtained polarizing film in the width direction (TD direction), with a length of 4 cm in the machine flow direction (MD direction) and 1.5 cm in the width direction (TD direction). For this measurement sample, a spectrophotometer equipped with an integrating sphere ("V7100" manufactured by Nihon Spectroscopic Corporation) was used to perform visual sensitivity correction in the visible light region with a 2° field of view and a C light source in accordance with JIS Z8722 (Method for Measuring Object Color), and then the single transmittance and polarization degree were measured. By the method described above, a polarization degree with a single transmittance of 44.0% was calculated.

[0155] (6) Shrinkage stress of polarizing film at high temperature

[0156] Shrinkage stress was measured using an Autograph AG-X equipped with a thermostat manufactured by Shimadzu Corporation. For the measurement, a polarizing film (15 cm in length direction, 1.5 cm in width direction) that had been humidified at 20 ℃ / 20 % RH for 18 hours was placed on a chuck (chuck spacing 5 cm), and the temperature of the thermostat was raised to 80 ℃ simultaneously with the start of tensioning. The polarizing film was tensioned at a speed of 1 mm / min, and tensioning was stopped when the tension reached 2 N, and the tension was measured from that state until 4 hours later. At this time, since the distance between the chucks changes due to the thermal expansion of the shaft, a mark seal was attached to the chuck, and the measurement was performed using a video-type elongation meter TR ViewX120S to adjust the distance between the chucks by the amount of movement of the mark seal attached to the chuck. In addition, the value obtained by subtracting the initial tension of 2 N from the tension measurement after 4 hours is defined as the shrinkage force of the modified film, and the value obtained by dividing that value by the sample cross-sectional area is defined as the shrinkage stress (N / mm²). 2 It was defined as ).

[0157] <Example 1>

[0158] A film-forming stock solution with a volatile fraction of 73 mass% was prepared, consisting of 100 mass parts of PVA obtained by saponifying polyvinyl acetate (degree of saponification 99.9 mol%, degree of polymerization 2400), 14 mass parts of glycerin as a plasticizer, 0.1 mass parts of lauric acid diethanolamide as a surfactant, and water. The filtered film-forming stock solution was then subjected to a shear rate of 207 s from a T-die. -1 The film was extruded onto a support (surface temperature 90°C) in the form of a film, and dried by spraying hot air at 85°C at a speed of 5 m / sec over the entire non-contact surface with the support. Subsequently, the film was peeled off from the support, and further dried between the first drying roll and the final drying roll (19th drying roll) located immediately before the heat treatment roll, so that one side and the other side of the PVA film alternately contacted each drying roll, and then peeled off from the final drying roll. At this time, the average surface temperature of each drying roll from the first drying roll to the final drying roll was set to 70°C. Finally, heat treatment was performed on a heat treatment roll with a surface temperature of 104°C, and then wound into a roll shape to obtain a PVA film (thickness 45 μm, width 3.3 m).

[0159] As a result of small-angle X-ray scattering measurements on the obtained PVA film, the crystal long period (Da) was 12.6 nm, the crystal long period (Ds) was 16.8 nm, and the crystal long period increase rate was 0.33. In addition, the swelling degree of the PVA film was measured to be 197%.

[0160] In addition, a polarizing film was manufactured using the obtained PVA film. At this time, the maximum elongation stress was 9.0 N / mm 2 ...was. As a result of measuring the optical performance of the obtained polarizing film, the single transmittance was 43.8% and the degree of polarization was 99.935%, and the degree of polarization was calculated to be 99.873% when the single transmittance was 44.0%. In addition, the shrinkage stress of the polarizing film was measured to be 43.7 N / mm2 was.

[0161] <Examples 2, 3 and Comparative Examples 1 to 4>

[0162] A PVA film was obtained in the same manner as in Example 1, except that the type of PVA, the amount of plasticizer, and the manufacturing conditions were changed as shown in Table 1. In addition, in Table 1, the ethylene modified with an ethylene unit content of 3 mol% was abbreviated as "ΔEt3".

[0163] The evaluation results of the obtained PVA films and polarizing films are shown in Table 1. In addition, for the polarizing films obtained in Examples 1 to 3 and Comparative Examples 1 to 3, a graph plotting the degree of polarization against shrinkage stress when the single transmittance is 44.0% is shown in Figure 2. In addition, the degree of swelling could not be measured because the PVA film of Comparative Example 4 was dissolved in distilled water at 30°C. In addition, the polarizing film could not be manufactured because the PVA film of Comparative Example 4 was dissolved in pure water (swelling treatment bath) at 25°C.

[0164]

[0165] As is evident from Table 1 and Figure 2, the polarizing film produced from the PVA film of the present invention has excellent optical performance and low shrinkage stress under high temperature. Explanation of the symbols

[0166] 1: Peak top of the scattering curve 2: Auxiliary line when setting the scattering vector q at the peak top of the scattering curve 3: Scattering vector q at the top of the scattering curve peak

Claims

Claim 1 A polyvinyl alcohol film in which the crystal long period (Ds) obtained from small-angle X-ray scattering measurements performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystal long period (Da) obtained from small-angle X-ray scattering measurements performed before immersion in the mixed solvent satisfy the following equation: 0.3 ≤ (Ds-Da) / Da < 0.5 Claim 2 A polyvinyl alcohol film according to claim 1, wherein the crystal long period (Da) is 10.0 to 12.5 nm. Claim 3 A polyvinyl alcohol film according to claim 1, wherein the polyvinyl alcohol contained in the polyvinyl alcohol film contains ethylene units, and the content thereof is 1 to 8 mol%. Claim 4 A polyvinyl alcohol film according to claim 1, wherein the average thickness of the film is 15 to 60 μm. Claim 5 In claim 1, a polyvinyl alcohol film that is a base film for manufacturing an optical film. Claim 6 A method for manufacturing an optical film by uniaxially stretching a polyvinyl alcohol film described in any one of claims 1 to 5. Claim 7 A method for manufacturing an optical film according to claim 6, comprising a swelling process for swelling a polyvinyl alcohol film.

Citation Information

Patent Citations

  • Producing method for polyvinyl alcohol-base polymer film

    JP2001315146A

  • Polyvinyl alcohol film and method for producing the same

    JP2006188655A

  • Polarizing film with small contraction stress and production method of the same

    JP2017142347A

  • Polyvinyl alcohol film and method for producing the same

    KR1020100049604A

  • Polyvinyl alcohol polymer film and process for producing same

    KR1020130124585A